Pengaruh Metode Permainan Untuk Melihat Hasil Belajar Siswa Pada Mata Pelajaran Bahasa Jawa Dikelas 5 SDN Japanan 2 Gudo Jombang - Sari, Angelita Kurnia; Pratiwi, Emy Yunita Rahma (Prodi Pendidikan Guru Sekolah Dasar, 2024)
The purpose of this study is to determine how the gaming approach affects grade V students at SDN Japanan 2 Gudo Jombang's general language learning. This study is quantitative, experimental in nature, and it employs a single group pretest-posttest methodology. There were twenty-four fifth-graders in the sample. In this study, tests and documentation were the approaches employed to acquire data. There are five essay questions and ten multiple-choice questions on this test. Out of the 24 students who studied using traditional techniques, the results indicated that 21 students 87.6% fell into the incomplete category and 3 students 12.4% fell into the complete category. In the traditional sense, it is not complete because the average score is 38.5, but in the context of game-based learning, no student falls into the complete category; instead, 24 students have a 100% completion rate. This indicates that the average score of 90 reaches the predicted KKM of 70, indicating that the learning is complete to a classically desirable degree. Examining game method's impact on student learning results reveals a strong correlation or influence. This is evident from the t test's significance result of 0.000 < 0.05. Hence alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected, indicating that the use of the game approach influences the learning results of students. According to the study's findings, students' learning outcomes—particularly those of the grade 5 pupils at SDN Japanan 2 Gudo have improved as a result of the application of the game approach.